2016
DOI: 10.18632/oncotarget.14334
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in ZNRD1-AS1 increase cancer risk in an Asian population

Abstract: Single nucleotide polymorphisms (SNPs) in human zinc ribbon domain containing 1 antisense RNA 1 (ZNRD1-AS1) have been associated with cancer development. In this meta-analysis, we more precisely estimated the associations between three expression quantitative trait loci SNPs in ZNRD1-AS1 (rs3757328, rs6940552, and rs9261204) and cancer susceptibility. The data for three SNPs were extracted from eligible studies, which included 5,293 patients and 5,440 controls. Overall, no significant associations between SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…SNP rs259919 was located in the lncRNA ZNRD1-AS1 region, which have reported to associated with bladder cancer, nasopharyngeal carcinoma, breast cancer, glioma, endometrial cancer, hepatocellular carcinoma, lung cancer, and cervical cancer. [15][16][17][18][19][20][21][22][23][24] Interestingly, we found rs3135001 was significantly associated with better efficacy of radiotherapy and fewer grade 3-4 oral mucositis. Using RegulomeDB 2.0, we found rs3135001 was located in a TF binding or DNase peak region.…”
Section: Discussionmentioning
confidence: 96%
“…SNP rs259919 was located in the lncRNA ZNRD1-AS1 region, which have reported to associated with bladder cancer, nasopharyngeal carcinoma, breast cancer, glioma, endometrial cancer, hepatocellular carcinoma, lung cancer, and cervical cancer. [15][16][17][18][19][20][21][22][23][24] Interestingly, we found rs3135001 was significantly associated with better efficacy of radiotherapy and fewer grade 3-4 oral mucositis. Using RegulomeDB 2.0, we found rs3135001 was located in a TF binding or DNase peak region.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it is essential to determine the molecular mechanism of lncRNAs to reduce the rate of vision loss of DR. ZNRD1-AS1, MEG3, OIP5-AS1 and TPTEP1 are the four key lncRNAs in the ceRNA network. ZNRD1-AS1 it is thought to be related to the progression of cancer (Li et al, 2016;Wang et al, 2017). Two recent studies showed that the expression of ZNRD1-AS1 is associated with the development and susceptibility of hepatocellular carcinoma and cervical cancer (Guo et al, 2015;Wen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis of B-NHL tumor microenvironment revealed different genetic characteristics related to the survival. 5 Functional single nucleotide polymorphisms (SNPs) can affect both the inflammatory microenvironment around the malignant tumor 6 and directly the malignant B cells. 7 Inflammasomes contain a number of cytoplasmic NOD-like receptors (NLR).…”
Section: Introductionmentioning
confidence: 99%